Prevalence of Metabolic Syndrome in Chronic Kidney Disease: A Hospital Based Cross-sectional Study - Poudel B, Gyawali P, Yadav BK, Nepal AK, Mahato RV, Jha B, Raut KB (Journal of Nepal Health Research Council, 2013)
Background: The components of metabolic syndrome (MetS) are the established risk factors of chronic kidney disease (CKD). Therefore, MetS and interplay of its various components, have deleterious effects on patients with chronic kidney disease. The aims of our study was to find out the prevalence of MetS in chronic kidney disease patients and to find out the association of each component of MetS with chronic kidney disease.Methods: A Hospital based cross-sectional study was carried out from February 2008 to August 2009. One hundred and sixty confirmed chronic kidney disease diagnosed patients were included in this study. Chronic kidney disease was defined from national kidney foundation guidelines. Anthropometric measurements of subjects were noted in a semi-structured pro-forma. Fasting blood sample was collected for the estimation of fasting blood glucose, triglyceride and HDL-cholesterol. Chronic kidney disease patients were diagnosed as having the metabolic syndrome by using the modified National Cholesterol Education Program Adult Treatment Program III criteria. Data were assessed by the t-test and Chi Square Test.Results: Sixty (37.5%) of the chronic kidney disease patients had MetS according to modified National Cholesterol Education Program Adult Treatment Program III criteria. The prevalence of hypertension, high fasting blood glucose, high triglyceride, low HDL Cholesterol and high waist circumference in chronic kidney disease patients was 112 (70.0%), 36 (22.5%), 74(46.25%), 98 (61.25%) and 30 (18.75%) respectively. Among the five components of the metabolic syndrome, waist circumference has the highest positive predictive value (73.34%) for chronic kidney disease.Conclusions: MetS occurs in more than one-third of chronic kidney disease patients. The prevalence of individual components of MetS is higher in chronic kidney disease patients.